Nip it in the bud: the impact of China’s large-scale free physical examination program on health care expenditures for elderly people - Qingshan Ma; Yuanmeng Zhang; Feng Hu; Haiyan Zhou; Hao Hu (Humanities & Social Sciences Communications)
Abstract In this study, we take China’s large-scale free physical examination program for people aged 65 and above as an entry point and use data from the China Health and Retirement Longitudinal Study (CHARLS) between 2011 and 2018 to construct a staggered difference-in-differences (DID) model to examine whether the free physical examination program affected elderly individuals’ health care expenditures. We find that the program increased the probability of attending a physical examination by 4.3%, reduced overall medical expenditures by 28.4%, and reduced hospitalization costs by 22.1% for persons over 65 years of age but did not have a significant effect on outpatient expenditures. The program produces results through two mechanisms: disease prevention and disease screening. The program is more effective in reducing medical expenses for older adults who live in rural areas, are younger, have lower educational levels, and have chronic illnesses. The benefits of the program’s implementation far outweigh its costs.